Effectiveness Aromatic Ginger With Lemongrass Hydrotherapy On Reducing Blood Pressure In Mild Preeclampsia Pregnant Women - sukini, tuti; Rahmawati, Ulya; Maryani, Siti; Idhayanti, Ribkha Itha (Midwifery and Nursing Research, 2024)
Background: The third leading cause of maternal death in Indonesia is preeclampsia, with 1,077 cases, a 2-fold increase from the previous year. Several interventions were carried out to reduce high blood pressure in pregnant women non-pharmacologically including aromatic ginger hydrotherapy and lemongrass. This therapy is easy to do independently and ingredients are easy to find in society.Research Objectives: The aims of this study were to identify blood pressure before and after intervention and to determine the effectiveness of kencur hydrotherapy with lemongrass in reducing blood pressure in pregnant women with mild preeclampsia.Research Methods: This research was conducted in the district of Magelang. This type of quantitative research with Quasy Experimental designs using a two group pretest posttest approach. The sample in this study were pregnant women with mild preeclampsia at the Muntilan 1 Public Health Center. The sampling technique used total sampling.Research Results: The results of the Independent t-test analysis, systolic blood pressure before and after treatment obtained p value (0.000) α (0.05), while diastolic blood pressure obtained p value (0.033) α (0.05) means there is significant difference between the kencur group and the lemongrass group. From the results of the analysis, the mean difference was 5,750, thus kencur hydrotherapy was more effective than lemongrass hydrotherapy.Conclusion: The results of this study are expected that health workers can provide socialization to pregnant women with mild preeclampsia to apply non-pharmacological treatment, namely with aromatic ginger hydrotherapy so that it can reduce blood pressure.